Probing the in-air growth of large area of 3D functional structures into a 2D supramolecular nanoporous network. Issue 72 (23rd August 2018) - Brisse, Romain; Guianvarc'h, Dominique; Mansuy, Christelle; Sagan, Sandrine; Kreher, David; Sosa-Vargas, Lydia; Hamitouche, Lydia; Humblot, Vincent; Arfaoui, Imad; Labet, Vanessa; Paris, Céline; Petit, Christophe; et al.
Abstract : 2D host–guest chemistry combined with drop-casting allows to trap functionalized 3D Zn–phthalocyanine complex into a large 2D porous supramolecular template. Abstract : Surface-confined host–guest chemistry at the air/solid interface is used for trapping a functionalized 3D Zn–phthalocyanine complex into a 2D porous supramolecular template allowing the large area functionalization of an sp 2 -hybridized carbon-based substrate as evidenced by STM, resonance Raman spectroscopy, and water contact angle measurements.